Abuse of Authority as Reviewed from the Perspective of State Administrative Law - Dwi Putri Aditya (Program Pascasarjana UIN Sumatera Utara Medan, 2021)
Abuse of authority is a fundamental problem in governance that has the potential to undermine the general principles of good governance (AUPB) and reduce public trust in the state bureaucracy. This phenomenon arises when government officials use their authority excessively, mix up their authority, or act arbitrarily, thus deviating from the purpose for which the authority was granted. This study aims to analyze abuse of authority from the perspective of State Administrative Law and examine the legal implications and oversight mechanisms available in the Indonesian legal system. The research method used is normative legal research with a library research approach, through a review of relevant laws and regulations, legal doctrine, and national scientific journals. The approach used includes a statute approach and a conceptual approach to obtain a comprehensive understanding. The results of the study indicate that Law Number 30 of 2014 concerning State Administration has provided a clear normative basis regarding the prohibition of abuse of authority, including review by the State Administrative Court. In addition, strengthening internal and external oversight mechanisms and the application of the principles of accountability and transparency are strategic steps in preventing abuse of authority. This research is expected to provide theoretical and practical contributions in efforts to realize good governance.